Self-seeded FEL wavelength extension with high-gain harmonic generation. (September 2016) - Zeng 曾, Ling 凌; Qin 秦, Weilun 伟伦; Zhao 赵, Gang 刚; Huang 黄, Senlin 森林; Ding, Yuantao; Huang, Zhirong; Marcus, Gabriel; Liu 刘, Kexin 克新
Abstract: We study a self-seeded high-gain harmonic generation (HGHG) free-electron laser (FEL) scheme to extend the wavelength of a soft X-ray FEL. This scheme uses a regular self-seeding monochromator to generate a seed laser at the wavelength of 1.52 nm, followed by a HGHG configuration to produce coherent, narrow-bandwidth harmonic radiations at the GW level. The 2nd and 3rd harmonic radiation is investigated with start-to-end simulations. Detailed studies of the FEL performance and shot-to-shot fluctuations are presented.